Flame–Flame Interactions and Jet–Jet Interactions in Gas Turbine Swirl Combustors - Wei Wei; Xin Hui; Xin Xue; Qiang An; Shiyang Yu (Energies)
Annular combustors are widely used in newly developed aero-engines. Nevertheless, the development of annular combustors requires substantial air supplies and high-power heaters during testing, leading to high experimental costs. To reduce these costs during the design phase, researchers often simplify annular combustors into single-dome configurations using aerodynamic and thermodynamic similarity principles. A fundamental divergence exists between the boundary conditions of annular and simplified single-dome combustors, which is reviewed in this article. It highlights the limitations of single-dome model combustors in accurately representing the crucial features of annular combustors, particularly flame–flame interaction (FFI) and jet–jet interaction (JJI). FFI and JJI existing in annular combustors are observed to result in alternating flow patterns and the superposition of mass and energy transfer between adjacent domes, which can deteriorate flame stabilization and increase NOx emissions. This review emphasizes the characteristics of multi-dome combustors and notes a lack of research comparing single-dome and multi-dome combustors under engine-relevant conditions. Addressing this research gap in the future can better connect fundamental combustion research and engine development, providing more guidance for engine designers.